Postoperative complications and waiting time for surgical intervention after radiologically guided drainage of intra-abdominal abscess in patients with Crohn's disease. Issue 5 (14th September 2021) - El-Hussuna, A; Karer, M L M; Uldall Nielsen, N N; Mujukian, A; Fleshner, P R; Iesalnieks, I; Horesh, N; Kopylov, U; Jacoby, H; Al-Qaisi, H M; Colombo, F; Sampietro, G M; et al.
Abstract: Background: In patients with active Crohn's disease (CD), treatment of intra-abdominal abscess usually comprises antibiotics and radiologically guided percutaneous drainage (PD) preceding surgery. The aim of this study was to investigate the risk of postoperative complications and identify the optimal time interval for surgical intervention after PD. Methods: A multicentre, international, retrospective cohort study was carried out. Details of patients with diagnosis of CD who underwent ultrasonography- or CT-guided PD were retrieved from hospital records using international classification of disease (ICD-10) diagnosis code for CD combined with procedure code for PD. Clinical variables were retrieved and the following outcomes were measured: 30-day postoperative overall complications, intra-abdominal septic complications, unplanned intraoperative adverse events, surgical-site infections, sepsis and pathological postoperative ileus, in addition to abscess recurrence. Patients were categorized into three groups according to the length of the interval from PD to surgery (1–14 days, 15–30 days and more than 30 days) for comparison of outcomes. Results: The cohort comprised 335 CD patients with PD followed by surgery. Median age was 33 (i.q.r. 24–44) years, 152 (45.4 per cent) were females, and median disease duration was 9 (i.q.r. 3.6–15) years. Overall, the 30-day postoperative complications rate was 32.2 per cent and the mortality rate was 1.5 per cent. After adjustment for co-variables, older age (odds ratio 1.03 (95 per cent c.i. 1.01 to 1.06), P < 0.012), residual abscess after PD (odds ratio 0.374 (95 per cent c.i. 0.19 to 0.74), P < 0.014), smoking (odds ratio 1.89 (95 per cent c.i. 1.01 to 3.53), P = 0.049) and low serum albumin concentration (odds ratio 0.921 (95 per cent c.i. 0.89 to 0.96), P < 0.001) were associated with higher rates of postoperative complications. A short waiting interval, less than 2 weeks after PD, was associated with a high incidence of abscess recurrence (odds ratio 0.59 (95 per cent c.i. 0.36 to 0.96), P = 0.042). Conclusion: Smoking, low serum albumin concentration and older age were significantly associated with postoperative complications. An interval of at least 2 weeks after successful PD correlated with reduced risk of abscess recurrence. Abstract : The authors showed that the optimal time interval for surgery is at least 2 weeks after drainage of the abscess. They confirmed the findings of other studies that smoking, steroid treatment and low albumin concentration in peripheral blood increase the risk of postoperative.